1996
DOI: 10.1038/383637a0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin-related protein RanBP2 acts as chaperone for red/green opsin

Abstract: Cyclophilins are ubiquitous and abundant proteins that exhibit peptidyl prolyl cis-trans isomerization (PPlase) activity in vitro. Their functions in vivo, however, are not well understood. Two new retinal cyclophilin isoforms, types I and II, are highly expressed in cone photoreceptors of the vertebrate retina. Type-II cyclophilin is identical to RanBP2, a large protein that binds the GTPase Ran. Here we report that two contiguous domains in RanBP2, Ran-binding domain 4 (RBD4) and cyclophilin, act in concert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
197
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 203 publications
(207 citation statements)
references
References 27 publications
7
197
3
Order By: Relevance
“…We have demonstrated that, whereas the transport from the ER to the cell surface of AT1R and β 2 -AR is dependent on Rab1, α 2B -AR export is independent of Rab1, indicating that different G protein-coupled receptors may use distinct pathways for their transport from the ER to the cell surface [23]. We then identified a motif consisting of a phenylalanine and double leucine spaced by 6 residues [F(x) 6 LL] in the membrane-proximal carboxyl termini of α 2B -AR and AT1R, which is essential for the exit of the receptors from the ER [22]. The receptor mutants, α 2B -ARm and AT1Rm in which the F(x) 6 LL motif were mutated to alanines, were unable to transport to the cell surface and were retained in the ER.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have demonstrated that, whereas the transport from the ER to the cell surface of AT1R and β 2 -AR is dependent on Rab1, α 2B -AR export is independent of Rab1, indicating that different G protein-coupled receptors may use distinct pathways for their transport from the ER to the cell surface [23]. We then identified a motif consisting of a phenylalanine and double leucine spaced by 6 residues [F(x) 6 LL] in the membrane-proximal carboxyl termini of α 2B -AR and AT1R, which is essential for the exit of the receptors from the ER [22]. The receptor mutants, α 2B -ARm and AT1Rm in which the F(x) 6 LL motif were mutated to alanines, were unable to transport to the cell surface and were retained in the ER.…”
Section: Discussionmentioning
confidence: 99%
“…We then identified a motif consisting of a phenylalanine and double leucine spaced by 6 residues [F(x) 6 LL] in the membrane-proximal carboxyl termini of α 2B -AR and AT1R, which is essential for the exit of the receptors from the ER [22]. The receptor mutants, α 2B -ARm and AT1Rm in which the F(x) 6 LL motif were mutated to alanines, were unable to transport to the cell surface and were retained in the ER. In this report, we sought to determine if α 2B -ARm could regulate the cell-surface targeting and signaling of its WT counterpart.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations